Determination of Mudharabah Savings at Sharia Commercial Banks in Indonesia - Deni Deni; Mardi Mardi; Itah Miftahul Ulum (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
This study aims to analyze the impact of economic variables on mudharabah savings in an Islamic financial environment. The main focus of this study is on three key factors: people's income, profit sharing rate, and inflation rate. The approach applied is quantitative as continuous data or time series.  The sources collected are secondary data from various Islamic banking institutions obtained in the financial statements released by the Otoritas Jasa Keuangan from 2017 to 2022, so that a sample of 7 Islamic commercial banks was obtained by purposive sampling processed and analyzed using SPSS 25 software. Overall, this study explores the variables of public income, profit sharing rate, and inflation on mudharabah savings. Based on the explanation of the findings of this study, it is revealed that partially the variables of public income and profit sharing rate have a significant influence on mudharabah savings, while in this context there is no evidence to suggest that inflation has an effect on mudharabah savings.